Calculation method for the fail-safe design of steel-steel contacts subject to fretting fatigue based on a worst-case assumption. (December 2022) - Knabner, Denny; Hauschild, Sven; Suchý, Lukáš; Vetter, Sebastian; Leidich, Erhard; Hasse, Alexander
Hightlights: Investigations on a slip-controled fretting fatigue test bench with flat pads. Separate analysis of the parameters of slip amplitude and contact pressure. Development of a robust calculation method for fretting fatigue. Validation of the calculation method on real life component connections. Good accuracy with an max. error of 14% in determination of the degree of utilization. Abstract: The lower fretting-fatigue strengths of component connections compared to plain fatigue strengths is a notable characteristic of strength assessments. It can be attributed to the additional tribological stress, which is dependent on the contact pressure, the slip amplitude and the selected material pairing. By using a double-actuated flat-pad test bench with slip control, a separate analysis of these influencing variables can be carried out. The materials investigated are limited to the class of steel materials, specifically to C22 + N, C45 + N, C45 + QT, 34CrNiMo6 + QT, and 42CrMo4 + QT, because of their frequent use in shaft–hub connections. Using fretting factors derived from the flat-pad tests, a local approach within the framework of the FKM guideline (Analytical strength assessment of components in mechanical engineering) was proposed for fail-safe design where there is fretting fatigue. The tribological stress parameters of slip amplitude and contact pressure are taken into account by means of a worst-case-concept. The critical stress parameters were found at a contact pressure of 40 M P a and a slip amplitude of 10 μ m . The calculation method was validated on a connecting-rod connection with a maximum error of 14 % in the determination of the degree of utilization.